MOVEMENTS OF ANATOMICAL COMPLEX: CONDYLAR PROCESS, TEMPOROMANDIBULAR JOINT, TEMPORAL BONE - R.S. Palyvoda; A.S. Volovar; A.V. Malikov (Український стоматологічний альманах)
Based on the fundamental manuscripts and inventions, structure of organs depends on their functions. Each maxillo-facial surgeon should know basics of anatomic relationships of human body, especially maxilla-facial area. Scientists also could prove importance of methods of diagnosis and treatment using anatomy field research based on evidence. One of the objective way to understand structure of organ, investigate changes of tissues, improve your practical skills to make the cadavers dissection.